Ultra-deep tyrosine phosphoproteomics enabled by a phosphotyrosine superbinder - Bian, Yangyang; Li, Lei; Dong, Mingming; Liu, Xuguang; Kaneko, Tomonori; Cheng, Kai; Liu, Huadong; Voss, Courtney; Cao, Xuan; Wang, Yan; Litchfield, David; Ye, Mingliang; et al. (Nature chemical biology, 2016)
A SH2-domain-derived superbinder that exhibits strong affinity for phosphotyrosine (pTyr) was used in conjugation with mass spectroscopy approaches to enrich and enable identification of pTyr sites in different cancer cell lines. We present a new strategy for systematic identification of phosphotyrosine (pTyr) by affinity purification mass spectrometry (AP-MS) using a Src homology 2 (SH2)-domain-derived pTyr superbinder as the affinity reagent. The superbinder allows for markedly deeper coverage of the Tyr phosphoproteome than anti-pTyr antibodies when an optimal amount is used. We identified ∼20,000 distinct phosphotyrosyl peptides and >10,000 pTyr sites, of which 36% were 'novel', from nine human cell lines using the superbinder approach. Tyrosine kinases, SH2 domains and phosphotyrosine phosphatases were preferably phosphorylated, suggesting that the toolkit of kinase signaling is subject to intensive regulation by phosphorylation. Cell-type-specific global kinase activation patterns inferred from label-free quantitation of Tyr phosphorylation guided the design of experiments to inhibit cancer cell proliferation by blocking the highly activated tyrosine kinases. Therefore, the superbinder is a highly efficient and cost-effective alternative to conventional antibodies for systematic and quantitative characterization of the tyrosine phosphoproteome under normal or pathological conditions.